CONDITIONS, OBJECTIVES, CONTENT, AND MEANS OF ENGLISH LANGUAGE TEACHING AT HIGHER EDUCATION INSTITUTIONS, LYCEUMS, AND COLLEGES - Mirfozilova Guloyim; Mo'ydinova Shohida (PEDAGOGS, 2025)
This article examines the essential conditions, pedagogical aims, content, and methods used in English Language Teaching (ELT) at higher education institutions, lyceums, and colleges, with a particular focus on the context of Uzbekistan. As English continues to gain global prominence, the demand for competent language instruction is growing rapidly across all levels of education. The article highlights the infrastructural and methodological requirements for effective ELT, including the need for qualified teachers, modern learning environments, and updated curricula. It also emphasizes the educational goals specific to each level, discusses the composition of ELT syllabi, and evaluates the role of technology and communicative approaches in classroom settings. The study concludes that strengthening ELT through international standards and context-relevant strategies will produce graduates who are linguistically proficient and globally competitive.